Psychological Predictors of Anxiety and Depression in Parkinson's Disease: A Systematic Review. Issue 10 (8th April 2016) - Garlovsky, Jack K.; Overton, Paul G.; Simpson, Jane
Abstract : Objectives: Parkinson's disease (PD) is a neurodegenerative disorder, affecting the motor system with psychological difficulties also frequently reported. While explanations for psychological difficulties are historically situated within a biomedical framework, more recently the relevance of psychological determinants has become a research focus. This review therefore examines this relationship with the two most commonly reported psychological difficulties (anxiety and depression) in people with PD. Method: Databases were systematically searched up to December 17, 2013, identifying 24 studies meeting inclusion criteria. Results: Significant predictors of heightened anxiety and depression included increased emotion‐focused coping; less problem‐focused coping; lower perceived control; more dominant beliefs about PD as part of a person's identity and influence on life; less social support and more avoidant personality types. Conclusions: Relationships between some specific psychological predictors and depression and anxiety seem well supported. The complexity of relationships between these psychological determinants should be taken into consideration when delivering psychological interventions.